A breastfeeding support program changed breastfeeding patterns but did not affect the mothers' self-efficacy in breastfeeding at two months. (December 2020) - Oras, Paola; Ljungberg, Tomas; Hellström-Westas, Lena; Funkquist, Eva-Lotta
Abstract: Background: Even though the biological norm in humans is frequent on demand breastfeeding, sparse feeding intervals have become the cultural norm in most Western countries due to a history of on schedule breastfeeding. This discrepancy between the biological basis and the culturally driven practice continues to interfere with women's ability to breastfeed. Aim: Our aim was to describe breastfeeding patterns in 2-month-old infants before and after the implementation of a breastfeeding support program. A secondary aim was to investigate the relationship between breastfeeding patterns and the mother's self-efficacy in breastfeeding. Methods: The study had a baseline/intervention design and was part of a larger project aiming to revive the Ten Steps to Successful Breastfeeding program. The larger project included breastfeeding training for health care professionals and provision of breastfeeding information to parents, including information about on demand breastfeeding. Data were gathered via breastfeeding diaries ( n  = 79 mothers from each group) and the Breastfeeding Self-efficacy Scale–Short Form ( n  = 83 in the baseline group and n  = 79 in the intervention group). Results: On demand breastfeeding patterns were more common in the intervention group (97.5%) than in the baseline group (74.7%) ( p  < 0.001), and breastfeeding sessions were more frequent in the intervention group (a median of 14 times per 24 h versus 11 times in the baseline group; p  = 0.026). Self-efficacy in breastfeeding did not differ between the groups, but was higher in mothers with exclusive breastfeeding. Conclusions: Knowledge about infants' breastfeeding behavior can strengthen on demand breastfeeding. Exclusive breastfeeding is associated with higher self-efficacy. Highlights: Breastfeeding support program increase on demand breastfeeding patterns Breastfeeding support program increase breastfeeding frequencies Fussy feeding behavior more common in on demand breastfeeding Shorter breastfeeding sessions in frequent feeding patterns High scores in Breastfeeding Self-Efficacy associated with exclusive breastfeeding